The Effect of Applying the Discovery Learning Method on Learning to Write Poetry Texts in Grade VIII at SMP N 1 Doloksanggul in the 2023/2024 Academic Year: Pengaruh Penerapan Metode Discovery Learning terhadap Pembelajaran Menulis Teks Puisi di Kelas VIII SMP N 1 Doloksanggul Tahun Pelajaran 2023/2024 - Ipan Sihite (PT. Batak Story Pedia, 2025)
This study aims to describe the effect of the application of the discovery learning method on the learning of writing poetry text by students of grade VIII SMP N 1 Doloksanggul in the 2023/2024 learning year. The population of this study were all VIII grade students of SMP N 1 Doloksanggul in the 2023/2024 Learning year which amounted to 240 people. the sample of this study was 30 people who represented the entire population while to determine the sample from the existing population with random sampling techniques (randomized random class). The research method used is the experimental method. to capture data Used to find the effect of certain treatments on learning to write poetry texts as many as 20 objective questions and assign students to write poetry texts. To determine the relationship between the two variables studied, the data analysis technique uses the correlation formula